Functional Reconstruction of Urogentital Tissue Defects Using Vascularized Composite Allotransplantation: A Novel Microsurgical Penis Transplant Model and Clinical & Histological Rejection Classification. (July 2018) - Fidder, Samuel; Furtmüller, Georg J; Simons, Brian; Kern, Barbara; Lough, Denver; Oh, Byoung Chol; Chicco, Maria; Brayton, Cory; Andrew Lee, WP; Cooney, Damon S.; Redett, Richard; Brandacher, Gerald
Abstract : Introduction: Defects of the male urogenital structures subsequent to major trauma are associated with impaired urinary and sexual function and result in a significantly reduced quality-of-life. Modern reconstructive methods employ autologous tissue-based reconstructions and implant placement to reconstruct a functional phallus, but outcomes are frequently unsatisfactory. Penis transplantation has been successfully employed in the recent past and represents an exciting avenue for restoration of male urogenitalia and function by using "like-with-like" tissue, when no conventional options are available. However, only little is currently known about the immunological features of these unique tissue grafts. Thus, to fill this critical void, we established a new animal model and clinical & histological rejection classification. Materials and Methods: In male 8-week old BN & Lewis rats the penis was dissected to design a penile graft based on the internal pudendal artery and dorsal penile vein including prepuce skin. A non-suture cuff technique was employed to perform end-to-end anastomosis of the graft vessels to the recipient inferior epigastric vessels. 30 syngeneic and allogeneic transplants were performed. Grafts were followed clinically and histologically at post-operative days (POD) 3, 5, 7, 9, 11, 13, 14, 16 and 18. Results: The graft design using anastomosis of the dorsal penile vein and the distal internal pudendal artery at the bifurcation into dorsal and deep penile arteries ensures optimal perfusion of the entire superficial and deep graft tissues. The non-suture cuff technique allows for successful microvascular anastomosis by a single surgeon in an average of 2.5 hours, at a 91% surgical success rate. Long-term graft survival (>POD 45) was observed in syngeneic transplants. Graft rejection follows a 4-stage clinical progression, indicating comparability to other skin containing VCAs. Graft rejection, however appears to be minimally delayed compared to hind limb allografts, with all untreated allografts fully rejected by POD 16. Histological analysis allowed for the development of a specific 4-grade rejection classification in analogy to the 2007 BANFF criteria for hand transplantation. Of note, graft skin and urethral lining tissue are first targets of rejection, which follows a distal to proximal pattern. Conclusion: We established a robust and reproducible murine model to study the immunobiology of urogenital tissue in the context of reconstructive transplantation. The graft design ensures vascular perfusion of all penile tissues. Heterotopic inset allows for standardized visual monitoring of graft viability. We propose a novel 4-grade histological rejection scale based on graft skin and urethral lining as the main targets of rejection.